2020
DOI: 10.21203/rs.3.rs-129772/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Entrepreneurial Networks, Entrepreneurial Orientation, and Performance of Small and Medium Enterprises: Are Dynamic Capabilities the Missing Link?

Abstract: Performance of small and medium enterprises (SMEs) has been addressed widely in the literature. Developed and developing both the countries are highly concerned about the growth and performance of small and medium enterprises. The literature over the performance is abundant, however, has certain controversies. To identify the reasons behind those controversies, this study has been conducted. the aim of the study was to identify the mediating role of dynamic capabilities which are developed by the entrepreneuri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…However, concrete evidence is still missing in literature as contrasting ndings are reported. For instance, positive results (Pratono 2018;Wang and Chung 2020;Al-Omoush et al, 2022) and negative ndings (Abu-Rumman et al, 2021;Ribeiro et al, 2021) have been reported in past literature. Therefore, a debate exists in the literature as to which types of networks yield bene ts to rm performance.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…However, concrete evidence is still missing in literature as contrasting ndings are reported. For instance, positive results (Pratono 2018;Wang and Chung 2020;Al-Omoush et al, 2022) and negative ndings (Abu-Rumman et al, 2021;Ribeiro et al, 2021) have been reported in past literature. Therefore, a debate exists in the literature as to which types of networks yield bene ts to rm performance.…”
mentioning
confidence: 84%
“…Small businesses utilize both their formal and informal networks to acquire resources (Mayanja et al, 2019), grow their markets (Zheng et al, 2020), as well as transact with other stakeholders like suppliers and creditors, which boosts their performance (Surangi, 2018). Several scholars (Pratono 2018;Anwar and Ali Shah, 2020;Abu-Rumman et al, 2021) have investigated the relationship between business networking and rm performance. However, concrete evidence is still missing in literature as contrasting ndings are reported.…”
Section: Entrepreneurial Networking and Small Business Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Entrepreneurial networks are strategic tools in achieving firm performance, and several scholars have studied the importance of networking, connections, and firm success (Abu-Rumman et al, 2020 ; Baum et al, 2000 ; Chu & Yoon, 2021 ; Daneil, 2010 ; Kalm, 2012 ; Karami & Tang, 2019 ; Madzimure, 2019 ; Raza et al, 2018 ; Rubino & Vitolla, 2018 ; Wang & Fang, 2021 ). The importance of entrepreneurial start-ups’ resources regarding networks is also recognized (Coviello, 2006 ; Hite & Hesterly, 2001 ).…”
Section: Introductionmentioning
confidence: 99%